Resistance of beef cattle of two genetic groups to ectoparasites and gastrointestinal nematodes in the state of São Paulo, Brazil - Oliveira, M. C S; Alencar, M. M.; Giglioti, R. [UNESP]; Beraldo, M. C D; Aníbal, F. F.; Correia, R. O.; Boschini, L.; Chagas, A. C S; Bilhassi, T. B. [UNESP]; Oliveira, H. N. [UNESP] (Elsevier, 2013)
The resistance to infestations by ectoparasites and infections by gastrointestinal nematodes was studied in 45 animals (males and females) of two genetic groups: purebred Nelore (NI, n=28) and Three-Cross (1/2 Angus+1/4 Canchim+1/4 Nelore - TC, n=17). The animals were monitored for 24months, during which they were left to graze in tropical pastures without receiving treatment for parasites. Each month the animals were examined for infestations by external parasites, to count the numbers of cattle ticks Rhipicephalus microplus with diameter greater than 4.5mm present on the left side, horn flies (Haematobia irritans) present in the lumbar region and botfly larvae (Dermatobia hominis) present on the entire body. The H. irritans counts were performed with the aid of digital photographs. At the time of examination, fecal samples were collected to count the eggs per gram (EPG) and to perform coprocultures, and peripheral blood samples were drawn to determine the packed cell volume (PCV) and to count the eosinophils. For statistical analysis, the count data were transformed into log10 (n+1), where n is the number of parasites. For PCV, significant effects (P<0.05) were found for collection month (CO), genetic group (GG) and gender (SX), with means and respective standard errors of 41.5±0.65% for the NI animals, 39.3±0.83% for the TC, 41.5±0.72% for the females and 39.3±0.77% for the males. Regarding the eosinophil counts, only the effect of sex was significant (P<0.01), with means and respective standard errors of 926.0±46.2/μL, for males and 1088.0±43.8/μL of blood, for females. The NI animals presented lower mean counts for all the external parasites compared to the TC animals (P<0.01). For ticks, the transformed means followed by standard errors for the NI and TC animals were 0.06±0.01 and 0.34±0.02, while for horn flies these were 0.92±0.05 and 1.36±0.06 and for botfly larvae they were 0.05±0.03 and 0.45±0.05, respectively. The average EPG values were only influenced by CO (P<0.01). The coprocultures revealed the presence of the following endoparasites: Haemonchus spp., Cooperia spp., Oesophagostomum spp. and Trichostrongylus spp., the last in smaller proportion. There were no significant differences between the genetic groups for the endoparasite loads, except for Cooperia spp., which were present in greater number (P<0.05) in the NI group. The results obtained in this experiment confirm previous findings of greater susceptibility of the Nelore breed to Cooperia spp. and high resistance to ectoparasites. © 2013 Elsevier B.V.
Keywords: Beef cattle; Ectoparasites; Nematodes; Resistance; arthropod larva; beef cattle; Brazil; Cooperia; Dermatobia; Diptera; ectoparasite; ectoparasitosis; eosinophil count; feces analysis; female; Haematobia irritans; Haemonchus; hematocrit; infection resistance; male; nematode; nematodiasis; nonhuman; Oesophagostomum; Oestridae; parasite load; pasture; Rhipicephalus (Boophilus) microplus; Trichostrongylus; Animalia; Boophilus microplus; Bos; Dermatobia hominis; Ixodida; Muscidae; Nematoda; Rhipicephalus